Studi Deskriptif Pengetahuan Lokal Masyarakat Tentang Bedda Lotong Sebagai Perawatan Kulit Tradisional Di Desa Mariorilau Kecamatan Marioriwawo Kabupaten Soppeng - Ramadhani, Mirna; Sumilih, Dimas Ario (Jurnal Kajian Sosial dan Budaya: Tebar Science, 2024)
This research aims to find out: How the people of Mariorilau Village can have local knowledge about skin care, How the people of Mariorilau Village pass on local knowledge about skin care to the next generation, and The interest of the people of Mariorilau Village in using bedda lotong as a work of local knowledge. Data collection techniques are primary data obtained through observation, interviews and documents/documentation from informants, and secondary data obtained through literature, journals and books. The sampling technique used snowball sampling and involved as many as 20 informants aged around 17-80 years. The results showed: (1) The spread of knowledge about the use of bedda lotong as a traditional skin treatment in Mariorilau Village began with a daughter of the Datu (King). (2) Mariorilau villagers teach their generation the knowledge of bedda lotong by passing it on by word of mouth and modeling how to make and use it. (3) Some people of Mariorilau Village still choose to use bedda lotong products that they concoct themselves rather than bedda lotong products produced with technologically advanced tools.